Cortical networks for auditory detection with and without informational masking: task effects and implications for conscious perception - Wiegand, Katrin; Heiland, Sabine; Uhlig, Christian Harm; Dykstra, Andrew R.; Gutschalk, Alexander (NeuroImage, 2018)
Ambiguous and masked stimuli have been used to study conscious perception by comparing neural activity during different percepts of identical physical stimuli. One limitation of this approach is that it typically requires a reporting task that may engage neural processes beyond those required for conscious perception. Here, we explored potential fMRI correlates of auditory conscious perception with and without overt report. In experiment 1, regular tone patterns were presented as targets under informational masking, and participants reported their percepts on each trial. In experiment 2, regular tone patterns were presented without masking, while the uninformed participants (i) passively fixated, (ii) performed an orthogonal visual task, and (iii) reported trial-wise the presence of the auditory pattern as in experiment 1 (in fixed order). Under informational masking, target-pattern detection was associated with activity in auditory cortex, superior temporal sulcus, and a distributed fronto-parieto-insular network. Unmasked and task-irrelevant tone patterns elicited activity that overlapped with the network observed under informational masking in auditory cortex, the right superior temporal sulcus, and the ventral precentral sulcus in an ROI analysis. We therefore consider these structures candidate regions for a neural substrate of auditory conscious perception. In contrast, activity in the intraparietal sulcus, insula, and dorsal precentral sulcus were only observed for unmasked tone patterns when they were task relevant. These areas therefore appear more closely related to task performance or top-down attention rather than auditory conscious perception, per se.
Available online 21 November 2017
Gesehen am 05.11.2018